2019
DOI: 10.3390/nano9121708
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Activity of Graphene Quantum Dots Prepared in Different Electrolyte Environments

Abstract: Antioxidants can reduce or inhibit damage such as oxidative decay caused by elevated levels of free radicals. Therefore, pursuing antioxidants with excellent properties has attracted more and more attention. Graphene quantum dots (GQDs) are considered a promising material because of their good free radical scavenging activity, low toxicity, and excellent water solubility. However, their scavenging efficiency, antioxidant mechanism, and effective control methods need to be improved. Herein, in order to further … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(8 citation statements)
references
References 58 publications
0
8
0
Order By: Relevance
“…It must be remembered that possible applications are limited not only to pure graphene; graphene derivatives such as graphene oxide and reduced graphene oxide are also included in the area of interest of biomedical use. Furthermore, graphene derivatives can be functionalized much easier by adding metal ions, molecules of metal oxides, as well as organic and inorganic polymers [ 4 , 5 , 6 ]. All these adjustments greatly expand the range of modifications of generated graphene nanocomposites, both as 3D and 2D materials, simultaneously opening vast possibilities of detection techniques.…”
Section: Introductionmentioning
confidence: 99%
“…It must be remembered that possible applications are limited not only to pure graphene; graphene derivatives such as graphene oxide and reduced graphene oxide are also included in the area of interest of biomedical use. Furthermore, graphene derivatives can be functionalized much easier by adding metal ions, molecules of metal oxides, as well as organic and inorganic polymers [ 4 , 5 , 6 ]. All these adjustments greatly expand the range of modifications of generated graphene nanocomposites, both as 3D and 2D materials, simultaneously opening vast possibilities of detection techniques.…”
Section: Introductionmentioning
confidence: 99%
“…DPPH is a stable nitrogen‐free radical‐containing molecule with a deep purple color that turns yellow upon reacting with antioxidant substances, resulting in a decrease in absorbance at 517 nm [45] . Previously, the antioxidant activity of CDs has been reported in many studies [46] . Here, we studied the antioxidant potential of different concentrations of W‐ and O‐CQDs using DPPH.…”
Section: Resultsmentioning
confidence: 99%
“…[45] Previously, the antioxidant activity of CDs has been reported in many studies. [46] Here, we studied the antioxidant potential of different concentrations of W-and O-CQDs using DPPH.…”
Section: Dpph Radical Scavenging Testmentioning
confidence: 99%
“…The statistical results indicate that the average particle diameters of GQDs-PBS, GQDs-NaOH, and GQDs-KCl are 3.19 ± 0.90, 3.76 ± 0.70, and 3.36 ± 0.70 nm, respectively. Furthermore, it has been reported that there is no significant difference in the shape or size of the samples, indicating that the three electrolytes have similar effects on the formation of GQDs [ 187 ].…”
Section: Diverse Approaches For the Modification Of Gqdsmentioning
confidence: 99%